Use of FEM to assess shrinkage cracking in restrained concrete structures - Leitão, L. (2012)
The present research has been motivated by the limitations of design codes in correctly estimating the necessary reinforcement for assuring adequate control of crack width associated to shrinkage. In view of such limitations, which frequently lead to overestimations of the necessary reinforcement, the present paper proposes an approach based on the finite element method and on a smeared crack model, in order to provide feasible estimations of crack distribution and crack width in laminar concrete structures subjected to partially restrained shrinkage deformations. Validation of the adopted approach is made through comparison of the model predictions with two distinct examples: (i) a concrete tie subjected to a direct tension test in laboratory; (ii) a real RC wall located in Portugal, cast 7 years ago. The validation examples show the feasibility of the proposed tool in view of estimating both crack distribution and crack width.